A rapid way of formulation development revealing potential synergic effects on numerous antimicrobial combinations against foodborne pathogens. (September 2021) - Ji, Jiali; Shankar, Shiv; Fernandez, Jorge; Juillet, Emma; Salmieri, Stephane; Lacroix, Monique
Abstract: The interactions between various essential oils (EOs) were evaluated for the development of antimicrobial formulations. A full factorial design was applied for testing eight EOs (Mustard, Thyme, Garlic, Oregano, Chinese cinnamon, Cinnamon bark, Red bergamot, Winter savory) against nine bacteria ( E.coli O157:H7 RM1239, E.coli O157:H7 RM 1931, E.coli O157:H7 RM 1933, E.coli O157:H7 RM 1934, E.coli O157:H7 380–94, Listeria monocytogenes LM 1045, Listeria innocua ATCC 51742, Salmonella Typhimurium SL 1344, Salmonella enterica Newport ATCC 6962) and two molds ( Penicillium chrysogenum ATCC 10106, Aspergillus niger ATCC 1015). Results showed that combinations of Thyme + Oregano, Oregano + Cinnamon bark, Chinese cinnamon + Cinnamon bark have shown high interactions in Factorial design and validated to be mostly additive effects against tested bacteria. The combination of Mustard + Thyme, Mustard + Garlic, and Thyme + Garlic EOs showed high interactions and also all additive effects against tested molds. The corresponding results of Factorial design and checkerboard render the designation to demonstrate the highly efficient formulations and interactions rapidly among abundant mixtures. Highlights: Antimicrobial activity of essential oils (EOs) evaluated against selected pathogens. Synergic effects of potent EOs in combinations were evaluated. Factorial design was used for synergistic antimicrobial formulation development.